Coastal management : changing coast, changing climate, changing minds - Baptiste, Alison (ICE Publishing, 2016)
The Institution of Civil Engineers Coastal Management conference series is the leading forum for the presentation of the latest developments in coastal engineering. The 8th conference took place in Amsterdam, The Netherlands, from 8-9 September 2015 and attracted delegates from over 30 countries. The proceedings of this conference comprise more than 70 peer-reviewed papers that present current issues, international research and practical applications.